2016
DOI: 10.14569/ijacsa.2016.070769
|View full text |Cite
|
Sign up to set email alerts
|

Conditions Facilitating the Aversion of Unpopular Norms: An Agent-Based Simulation Study

Abstract: Abstract-People mostly facilitate and manage their social lives adhering to the prevalent norms. There are some norms which are unpopular, yet people adhere to them. Ironically, people at individual level do not agree to these norms, but, they still follow and even facilitate them. Irrespective of the social and psychological reasons behind their persistence, sometimes, for societal good, it is necessary to oppose and possibly avert the unpopular norms. In this paper, we model theorydriven computational specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Ironically, in all cases depicted in Figure. 2, the population achieves stability always being attracted towards various fixed points. In our previous work [31], it was observed that in highly dense conditions with a large number of norm aversion ACTs, the aversion of unpopular norms can be achieved. This fact is highlighted in Figure. 3.…”
Section: Previous Findingsmentioning
confidence: 94%
See 4 more Smart Citations
“…Ironically, in all cases depicted in Figure. 2, the population achieves stability always being attracted towards various fixed points. In our previous work [31], it was observed that in highly dense conditions with a large number of norm aversion ACTs, the aversion of unpopular norms can be achieved. This fact is highlighted in Figure. 3.…”
Section: Previous Findingsmentioning
confidence: 94%
“…Though lots of work has been done on the emergence and prevalence of norms, very limited is carried out for the aversion of unpopular norms. To the best, our knowledge, our previous work [31,22,23] is the only agent-based study on this exciting research area. Willer et al have pointed out many "empirical cases in which individuals are persuaded to publicly support behaviors or beliefs that they privately question" [29].…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations